The Effect of Job Performance, Education, Training and Competence on Career Development at the Tebing Tinggi District Office - Irawati, Wiwin; Madjir , Sulbahri; Aprini , Nisma (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
This study aims to determine and analyze the effect of work performance, education, training, and competence on career development at the Tebing Tinggi sub-district office, either partially or simultaneously. This study uses quantitative research methods with respondents, namely employees of the Tebing Tinggi Sub-district Office, Empat Lawang Regency, a total of 33 respondents. Tests in this study used multiple linear regression analysis with the tools of the SPSS (Special Package and Service Solution) version 26 program. The results of the research show that work performance, education, training, and competence have proven to have a significant effect on employee career development at the Tebing Tinggi sub-district office, either partially or simultaneously.